Audel HVAC Fundamentals Volume 3 Air-Conditions, Heat, Pumps and Distribution Systems - BRUMBAUGH, James E (John Wiley & Sons, 2004)
Audel HVAC Fundamentals Volume 3 Air-Conditions, Heat, Pumps and Distribution Systems